Point based assessment: selecting the best way to represent landslide polygon as point frequency in landslide investigation - Norbert Simon, Michael Crozier, Mairead de Roiste, Abdul Ghani R, . (2013)
This study evaluates two common methods to represent landslide polygons as frequencies for use within GIS analysis. These methods are used to extract information from factor maps, such as a single value for slope angle for the landslide polygon, which is then used in hazard assessment. Understanding the errors associated with generating points to represent landslide polygons should be clearly understood to evaluate the effectiveness of these points.